2022
DOI: 10.1101/2022.01.04.21267659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Meta-analysis of COVID-19 patients to understand the key predictors of mortality in the non-vaccinated groups in remote settings

Abstract: Various studies have looked into the impact of the COVID-19 vaccine on large populations. However, very few studies have looked into the remote setting of hospitals where vaccination is challenging due to social structure, myths, and misconceptions. There is a consensus that elevated inflammatory markers such as CRP, ferritin, D-dimer correlate with increased severity of COVID-19 and are associated with worse outcomes. In the present study, through retrospective meta-analysis, we have looked into ~20 months of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Interestingly, in this case, it was also observed that male gender was a predictor of death, despite vaccination status [ 22 , 23 ], which may result from the fact that women are generally characterised by a better immune response to internal and external antigens than men [ 15 , 24 ], and this advantage can also be reflected in the effectiveness of the vaccinations in these two groups [ 25 ]. We also underline that higher levels of inflammation markers (CRP, ferritine, D-dimer) correlate with the increased severity of COVID-19 and are associated with worse results in these patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this case, it was also observed that male gender was a predictor of death, despite vaccination status [ 22 , 23 ], which may result from the fact that women are generally characterised by a better immune response to internal and external antigens than men [ 15 , 24 ], and this advantage can also be reflected in the effectiveness of the vaccinations in these two groups [ 25 ]. We also underline that higher levels of inflammation markers (CRP, ferritine, D-dimer) correlate with the increased severity of COVID-19 and are associated with worse results in these patients [ 26 ].…”
Section: Discussionmentioning
confidence: 99%